Insights into vitamin A in bladder cancer, lack of attention to gut microbiota? - Luo, Peiyue; Zheng, Liying; Zou, Junrong; Chen, Tao; Zou, Jun; Li, Wei; Chen, Qi; Qian, Biao (Frontiers in Immunology, 2023)
Vitamin A has long been associated with bladder cancer, and many exogenous vitamin A supplements, vitamin A derivatives, and synthetic drugs have been investigated over the years.However, the effectiveness of these strategies in clinical practice has not met expectations, and they have not been widely adopted. Recent medical research on intestinal flora has revealed that bladder cancer patients exhibit reduced serum vitamin A levels and an imba lance of gut microbiota. In light of the close relationship between gut microbiota and vitamin A, one can speculate that a complex regulatory mechanism exists between the two in the development and occurrence of bladder cancer.As such, further exploration of their interaction in bladder cancer may help guide the use of vitamin A for preventive purposes. During the course of this review, attention is paid to the influence of intestinal microbiota on the vitamin A metabolism and the RA signaling pathway, as well as the mutual promotion relationships between them in the prevention of bladder cancer，In addition, it emphasizes the importance of intestinal microbiota for bladder cancer prevention and treatment .